RANCANG BANGUN SISTEM DATABASE KUALITAS AIR LIMBAH RUMAH SAKIT - Wahjono, Heru Dwi (Center for Environmental Technology, 2007)
Environmental pollution that happened around us in this time have resided in condition of concerning. The environmental quality recovering is not only becoming responsibility of government, but becoming responsibility of all society, especially who was causing the environmental pollution itself. Some metropolitans like Jakarta has domestic waste as dominant waste, which is not dominant hostpital waste also contributes environmental pollution in Jakarta.To decrease the pollution level of wastewater from hospital, the government of Jakarta has published the environmental regulation. The regulation contains how the hospitals in Jakarta should manage and process their wastewater. This article explain about the design and development of database system for managing the data of hospital wastewater quality, so the observation process of wastewater quality from the wastewater treatment plant for the hospital can be monitored easily and known immediately.Ã‚Â Katakunci : database kualitas air, Ã‚Â kualitas air limbah rumah sakit, IPAL rumah sakit, sistem manajemen basis data.